Performance Analysis and Operation and Maintenance Cost Requirements for Rapak Di Drainage - Yusnita, Maya; Wulandari, Esti; Nugroho, Laksono Djoko (International Journal Labs, 2025)
Inadequate drainage infrastructure often leads to waterlogging during rainfall, emphasizing the need for urgent repairs. This study assesses the performance condition of the Rapak Dalam Drainage system using a quantitative and qualitative approach, including field observations, direct measurements, and hydrological data analysis. The findings indicate that the drainage system is rated at a